Adsorption of Chromium (VI) by Cu (I)-MOF in Water: Optimization, Kinetics, and Thermodynamics - Hongxue Qi; Xianjun Niu; Haipeng Wu; Xiuping Liu; Yongqiang Chen (Journal of Chemistry)
To investigate the adsorption behavior of Cu (I)-MOF material for chromium (VI) in water, the parameters of influencing adsorption were optimized and found as follows: the optimal pH was 6 for the adsorption of Cr (VI) by the Cu (I)-MOF, the optimal amount of adsorbent was 0.45 g·L−1, and the adsorption saturation time was within 180 min. Subsequently, the kinetics results were fitted by four models such as pseudo-first-order, pseudo-second-order, Elovich, and intraparticle diffusion models. Among them, the adsorption of chromium (VI) was more inclined to the pseudo-first-order model (Radj2 = 0.9230). Then, the isotherm data were fitted by Langmuir and Freundlich models. The results indicated that Langmuir isotherm was the excellent match model (Radj2 = 0.9827). It belongs to a monolayer adsorption, and the maximum adsorption capacity was 95.92 mg·g−1. Subsequently, the thermodynamic parameters of the adsorption were calculated as follows: enthalpy change (ΔHθ) was −8.583 kJ·mol−1, entropy change (ΔSθ) was −8.243 J·mol−1 K−1, and the Gibbs function change (ΔGθ) was less than zero in the temperature range of 288–328 K, indicating that the reaction was spontaneous. Finally, both the spectra of infrared and XPS supported the adsorption mechanism that belonged the ion exchange. The spectra of XRD and SEM images shown that the structure of Cu (I)-MOF remained stable for at least 3 cycles. In conclusion, Cu (I)-MOF material has a high adsorption capacity, good water stability, low cost, and easy to prepare in large quantities in practical application. It will be a promising adsorbent for the removal of Cr (VI) from water.